Visualisasi Aturan Asosiasi Berbasis Graph untuk Data Tindak Kejahatan - Eduardus Hardika Sandy Atmaja (Sanata Dharma University, 2017)
Criminality is a social problem causing negative impacts on society welfare. Police as law enforcement officer was required to take actions to prevent criminality which was increasingly widespread. Such efforts could be realized by analizing criminal data to obtain useful information for the preparation of criminal prevention strategies. However, extracting knowledge from criminal data effectively was a problematique for them. In this study, data mining was used to solve knowledge extraction problem from the dataset. The technique was aimed to get information about crime patternsby analyzing criminal activity habits. Association rule mining and apriori algorithm were used to find crime patterns. Generating crime patterns in data mining was difficult to understand when there were too many rules. Graph based visualization of association rules designed to solve that problem. Generated visualization showed relationship between crimes. That visualization was expected to help the police to understand the crime pattern so they could do prevention efforts more effectively. The results showed that the visualization of association rules could present association rules in more interesting way and described the crime pattern.